2016
DOI: 10.1001/jamapediatrics.2016.0845
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Maternal Prepregnancy Body Mass Index and Plasma Folate Concentrations With Child Metabolic Health

Abstract: IMPORTANCE Previous reports have linked maternal prepregnancy obesity with low folate concentrations and child overweight or obesity (OWO) in separate studies. To our knowledge, the role of maternal folate concentrations, alone or in combination with maternal OWO, in child metabolic health has not been examined in a prospective birth cohort.OBJECTIVE To test the hypotheses that maternal folate concentrations can significantly affect child metabolic health and that sufficient maternal folate concentrations can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 37 publications
2
66
0
6
Order By: Relevance
“…The study included mother–infant pairs who were recruited at the Boston Medical Center (BMC) at the time of birth from 1998 to 2013 and followed up prospectively from 2003 to 2015 (Figure ), as described elsewhere . Children who were not intending to receive paediatric care at the BMC were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study included mother–infant pairs who were recruited at the Boston Medical Center (BMC) at the time of birth from 1998 to 2013 and followed up prospectively from 2003 to 2015 (Figure ), as described elsewhere . Children who were not intending to receive paediatric care at the BMC were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…A recent NHANES study showed that unmetabolized folic acid (either from folic acid supplementation or fortified grain products) has been detected in most of the U.S. population . Furthermore, data from the Boston Birth Cohort showed a wide range of individual variation in plasma folate levels ranging from insufficient to excessive levels . The association between folic acid intake during pregnancy and ASD risk in offspring has been equivocal.…”
mentioning
confidence: 99%
“…11 In addition, maternal cardiometabolic risk factors (obesity, hypertensive-disorder, diabetes), poor birth outcome and maternal nutrition in the 3 rd trimester are associated with cardiovascular health in childhood. 32 Although we did not measure fetal Hcy concentrations, a previous study has suggested that the maternal Hcy level is the primary predictor of blood Hcy in the developing fetus. 46 In our study, we based maternal prepregnancy BMI on selfreported height and weight, thus it may have been subject to reporting bias that led to a misclassification for overweight and obesity.…”
Section: Discussionmentioning
confidence: 95%
“…While, results of one study showed that, the squat serum folate level interconnected with obesity might be a result of less folate consumption or volumetric dilution of blood in obese subjects. Additionally, adiposity can effect on uptake of folate via intestinal epithelium (Wang et al, ). So, enhanced level of serum folate played an important role in the management of obesity.…”
Section: Discussionmentioning
confidence: 99%